Health care and contraceptive decision-making autonomy and use of female sterilisation among married women in Malawi - Alhassan, Nurudeen (Frontiers in Global Women's Health, 2024)
Introduction: Female sterilisation is the most common contraceptive method used globally. The use of female sterilisation is disproportionately low in sub-Sahara Africa (SSA) at just 1%. Nonetheless, the prevalence of sterilisation among married women in Malawi is quite high at about 11%. While a few recent studies in SSA have examined the relationship between women's decision-making autonomy and use of long-acting contraceptives, very few have investigated whether different dimensions of decision-making autonomy predict the use of female sterilisation differently. The objective of this study was therefore to examine the relationship between health care and contraceptive decisionmaking autonomy and the use of female sterilisation in Malawi.The study relied on secondary data from the 2015-16 Malawi Demographic and Health Survey. The sample comprised 9,164 married women in Malawi that were using a modern contraceptive. Multinomial logistic regression analysis was used to examine the association between health care and contraceptive decision-making autonomy and the use of female sterilisation, controlling for key socio-demographic characteristics.The study revealed that the percentage of married women that made health care and contraceptive decisions independently was quite low. The main finding of this study was that contraceptive decision-making autonomy increased the relative likelihood of using female sterilisation while health care autonomy was associated with a lower likelihood of being sterilized. The sociodemographic characteristics that significantly predicted the use of female sterilisation included age, place of residence, household wealth and the number of children a woman had.This study demonstrates that health care and contraceptive decision making have different effects on the use of female sterilisation among married women in Malawi. Specifically, women with autonomy in health care decision making had a relatively lower likelihood of using female sterilisation while those with contraceptive decision-making autonomy had a higher likelihood of using female sterilisation. This suggests that intervention aimed at increasing the uptake of female sterilisation in Malawi need to focus on empowering women in the contraceptive decision-making domain.